An addiction‐based digital weight loss intervention: A multi‐centre randomized controlled trial. Issue 3 (9th December 2022) - Vidmar, Alaina P.; Salvy, Sarah J.; Wee, Choo Phei; Pretlow, Robert; Fox, D. Steven; Yee, Jennifer K.; Garell, Cambria; Glasner, Suzette; Mittelman, Steven D.
Summary: Objective: This randomized clinical trial tested the effectiveness of an addiction‐based digital weight‐loss intervention, focusing on withdrawal/abstinence from self‐identified problem foods, snacking and excessive amounts at meals, and discomfort displacement, with and without coaching, compared to an in‐person, multi‐disciplinary, care model among adolescents with obesity. We hypothesized that the digital intervention with coaching would yield greater weight loss and lower delivery burden than the standard clinical arm, and greater participant engagement than the digital arm without coaching. Methods: Adolescents were randomized to app intervention, with or without coaching, or in‐person multidisciplinary obesity intervention for 6 months. The primary outcome was change in %BMIp95 at weeks 12 and 24. A mixed‐effects linear regression model was used to assess the association between change in %BMIp95 and intervention arm. We were also interested in assessing delivery burden, participant engagement and evaluating the relationships between weight change and demographic characteristics, mood, executive function and eating behaviours. Results: All adolescents ( n  = 161; BMI ≥95th%, age 16 ± 2.5 year; 47% Hispanic, 65% female, 59% publicly insured) lost weight over 24‐weeks (−1.29%, [−1.82, −0.76], p  < 0.0001), with no significant weight loss difference between groups ( p  = 0.3). Girls lost more weight than boys, whereas binge eating behaviour at baseline was associated with increase in %BMIp95 when controlling for other covariates. There was no association between ethnicity, mood, timing of intervention in relation to the pandemic, or executive function and change in %BMIp95 . Conclusions: Contrary with our hypothesis, our results showed no difference in the change in BMI status between treatment arms. Since efficacy of this digital intervention was not inferior to in‐person, multi‐disciplinary care, this could offer a reasonable weight management option for clinicians, based on youth and family specific characteristics, such as accessibility, resources, and communication styles. Clinical Trial Registration : ClinicalTrials.gov identifier: NCT035008353